Effects of hypohydration on repeated 40-yd sprint performance - Gann, J. J.; Green, J. M.; O'Neal, E. K.; Renfroe, L. G.; Andre, T. L. (The Journal of Strength and Conditioning Research, 2016)
This study examined the effects of hypohydration on repeated 40-yd sprint performance. Anaerobically fit current and former Division II male athletes (n = 12) completed 2 bouts of 10 × 40-yd sprints followed by an agility test, dehydrated (~3% body weight [DT]), or hydrated trial (HT). Statistical analysis of group means indicated that hypohydration had little effect on sprint times for either the first (DT= 5.38 ± 0.37; HT = 5.35 ± 0.34) or second (DT = 5.47 ± 0.39; HT = 5.42 ± 0.39) bout of 10 sprints with only sprint number 2, 5, and 6 of bout 2 reaching statistical significance. However, when individual sprint performance was considered, a greater effect was seen. In all, 83% (10 of 12) of subjects experienced a meaningful change (=0.1 seconds) (positive or negative) in mean sprint time (DT vs. HT) for one or more bout of 10 sprints. Ratings of perceived exertion was significantly higher (~1 unit on a 10 point scale) for DT in all sprints during bout 1 and the first 2 sprints of bout 2. These results indicate that the effect of hypohydration on repeated sprint performance varies among individuals. Some improved performance with hypohydration, while others experienced detrimental effects. Hypohydration also resulted in a particularly notable negative impact on perceptual measures of exertion even when performance was similar.